Peran Lingkungan dan Informasi dalam Keputusan Siswa Memilih Pendidikan Kejuruan: Studi Kasus Siswa Kelas XII di Madrasah Aliyah Techno Scientist Terkemuka di Malang - Luhur Adi Prasetya; Nabil Achmad Aufani; Abdur Rahman Frima (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
This study aims to explore the factors that influence students' decisions to pursue vocational education in grade XII of the Techno Scientist Excellent Madrasah Aliyah by using qualitative methods through interviews with eight students. The findings show that students are mainly motivated by the aspiration to acquire practical skills that are in line with the demands of the world of work. The main influencing factors include parental encouragement, teacher guidance, and peer influence, with teachers playing an important role as the main source of information regarding vocational prospects. However, students face challenges due to limited socialization efforts from both schools and government agencies, resulting in a lack of awareness about the benefits of vocational education. This gap contributes to the continued negative stigma surrounding vocational pathways. Students expressed the need for broader promotional efforts to improve public perception and strengthen their understanding of vocational training as a viable and strategic pathway to employment. Addressing this issue can significantly improve student engagement and community acceptance of vocational education.